Análisis de la Contaminación Acústica Producida por Talleres Textiles en la Comunidad de Quinchuquí - Morales Teran, Inti Raymi (2024)
Quinchuquí is an indigenous community belonging to the parish of Dr. Miguel Egas Cabezas, located in the canton of Otavalo, province of Imbabura. The community has experienced a growth of textile activity, causing a problem regarding the noise generated by the machinery used in the production processes. The main objective of the present work is to analyze the noise pollution generated by the textile workshops located in the community of Quinchuquí, through a qualitative and quantitative research approach. Five textile workshops of interest were selected for the study, assigning five measurement points to each workshop, inside and outside of them. The measurement criteria were carried out according to the regulations of the Ministry of the Environment of Ecuador. Surveys of workers and inhabitants of the areas surrounding the textile workshops were used to determine their perception of noise. The noise levels produced by these textile activities in the selected workshops were evaluated, comparing them with Ecuador's regulations, which establish the maximum permissible limits, according to the type of land use of the site under study. It is evident that the points closest to the textile workshops exceeded the regulations on the maximum permissible noise emission limits, exceeding the limit of 55 dB, with noise levels reaching 90.4 dB in the areas closest to the noise source, and 34.7 dB in the areas farthest from the workshops. The implementation of measures within the workshops is proposed, such as soundproofing by means of panels placed on the walls and maintenance of machinery, which will help mitigate noise levels, improving the sound environment of the community. This study contributes to the knowledge about noise pollution in industrial contexts and its relationship with environmental sustainability and the well-being of the population.